New species and records of Trypetinae (Diptera: Tephritidae) from China - Chen, Xiao-Lin; Wang, Xin-Jian; Zhu, Chao-Dong (Zootaxa, 2013)
Eight new species of Trypetinae (Diptera: Tephritidae) from China are described and illustrated. The new species are Cornutrypeta chishuiensis Chen sp. nov., C. motuonia Chen sp. nov., Hoplandromyia hubeiensis Chen sp. nov., H. motuonica Chen sp. nov., Magnimyiolia disrupta Chen sp. nov., M. tengchongnica Chen sp. nov., M. tibetana Chen et Wang sp. nov. and M. yunnanica Chen et Wang sp. nov. Keys to the known species of the genera Cornutrypeta Han et Wang and Hoplandromyia Bezzi from the World, and the genera Magnimyiolia Shiraki from East Asia are updated and provided. C. spinifrons (Schroeder) is newly recorded from China, and the female of C. hunanica Chen et Wang is recorded, described and illustrated for the first time. Illustrations of the type of M. huanana Wang and a new distribution of C. hunanica Chen et Wang are provided.